Post-processing techniques using 3D Slicer for T1-weighted MRI analysis of radiochromic gel dosimeters. Issue 1 (1st January 2022) - Lee, Hannah J.; Dolan, James; Pencea, Stefan; Ibbott, Geoffrey S.
Abstract: Radiochromic FXG gel dosimeters were investigated for end-to-end validation of TG-119 plans delivered in the pre-clinical Elekta 1.5 T-7 MV FFF MR-Linac. Due to the noise levels in the T1-weighted MR images, this preliminary study investigated post-processing techniques available in 3D Slicer and their impact on gamma passing rates. Binomial blur and discrete Gaussian image filters were identified as the most impactful on increasing gamma passing rates for T1-weighted MR images; however, any application of image filters should be implemented with caution on the interpretation of the results.